1988
DOI: 10.1111/j.1476-5381.1988.tb11658.x
|View full text |Cite
|
Sign up to set email alerts
|

The negative inotropic effect of nicorandil is independent of cyclic GMP changes: a comparison with pinacidil and cromakalim in canine atrial muscle

Abstract: The negative inotropic effects of nicorandil, a nitrate with K‐channel opening properties, have been compared with those of pinacidil, cromakalim and nifedipine, in canine right atrial muscle. Cromakalim, pinacidil and nicorandil all produced a negative inotropic effect. However, even at their maximally effective concentrations, the force of contraction remained at about 10% of control levels, whereas contraction was abolished by nifedipine. The pD2 values for the negative inotropic effects of cromakalim, pina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…Pinacidil produced a dose-dependent negative inotropic response in rabbit left atrial strips, although it was less potent than has been found in dog atrium (Yanagisawa et al, 1988) and in cat right ventricular papillary muscle (Steinberg et al, 1988). The direct negative inotropic response to pinacidil is believed to be related to its ability to promote the efflux of potassium, which in turn may shorten the action potential duration and reduce the influx of calcium (Steinberg et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinacidil produced a dose-dependent negative inotropic response in rabbit left atrial strips, although it was less potent than has been found in dog atrium (Yanagisawa et al, 1988) and in cat right ventricular papillary muscle (Steinberg et al, 1988). The direct negative inotropic response to pinacidil is believed to be related to its ability to promote the efflux of potassium, which in turn may shorten the action potential duration and reduce the influx of calcium (Steinberg et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments pinacidil was dissolved in 0.1 N hydrochloric acid, as reported by Yanagisawa et al, (1988), to obtain a stock solution and further dilutions were made in modified Chenoweth-Koelle solution.…”
Section: Cyclic Nucleotide Determinationmentioning
confidence: 99%
“…ATP-sensitive K+-channel openers directly induce negative chronotropic and inotropic responses in heart preparations (Yanagisawa et al, 1988;1989;Murakami et al, 1992) but little is known about the role of the large-conductance Ca 2-activated K+-channels or other ChTX-sensitive K+-channels in heart, since no activators of these channels have yet been developed. In the present study, SCA40 produced dual effects on rat isolated atria.…”
Section: Rat Thoracic Aorta Studiesmentioning
confidence: 99%
“…Another important finding obtained in the present experiments was that the cardiodepressant effects of cromakalim and nicorandil, as reflected by decreases in LV dP/dt.., were also antagonized by glibenclamide. Decreases in LV dP/dtm.x produced by the two drugs were in all probability a result of their negative inotropic effect, because nicorandil Yanagisawa et al, 1988;1989) and cromakalim (Gotanda et al, 1988;1989;Yanagisawa et al, 1988;1989) have been known to produce a negative inotropic effect both in vivo and in vitro entirely by K-channel opening. Thus, the present findings can be taken to indicate that the specific antagonism by glibenclamide of cromakalim and nicorandil occurred in left ventricular muscle cells, too.…”
Section: Discussionmentioning
confidence: 99%
“…The vasodilator effects of cromakalim, a potent antihypertensive drug with vasodilator properties (Buckingham et al, 1986), have recently been shown to involve K-channel opening more specifically than nicorandil (Weir & Weston, 1986). Also, cromakalim lacks the ability to increase intracellular guanosine 3':5'-cyclic monophosphate (cyclic GMP) as seen with nicorandil (Yanagisawa et al, 1988). Recently, it has also been shown that in rats the vasodepressor effect of cromakalim on systemic arterial pressure was specifically antagonized by glibenclamide, an oral antidiabetic drug (Cavero et al, 1988).…”
Section: Introduction Methodsmentioning
confidence: 99%